2021
DOI: 10.1016/j.asmr.2021.07.008
|View full text |Cite
|
Sign up to set email alerts
|

The Majority of Complaints About Orthopedic Sports Surgeons on Yelp Are Nonclinical

Abstract: Purpose: To examine and characterize extremely negative Yelp reviews of orthopedic sports surgeons in the United States. Methods: A search for reviews was performed using the keywords "Orthopedic Sports Medicine" on Yelp.com for 8 major metropolitan areas. Single-star reviews were isolated for analysis, and individual complaints were then categorized as clinical or nonclinical. The reviews were classified as surgical or nonsurgical. Results: A total of 11,033 reviews were surveyed. Of these, 1,045 (9.5%) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 28 publications
(30 reference statements)
0
29
0
Order By: Relevance
“…Although most reviews did not reference clinical aspects of care, there was a much higher percentage of clinical complaints when compared with similar studies in other orthopaedic subspecialties. 18,20 Figure 2…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although most reviews did not reference clinical aspects of care, there was a much higher percentage of clinical complaints when compared with similar studies in other orthopaedic subspecialties. 18,20 Figure 2…”
Section: Discussionmentioning
confidence: 99%
“…23 Although a surgeon's technical skills may be excellent, their online ratings might not reflect this because nonclinical factors, such as wait time, physician bedside manner, and parking, are more associated with negative reviews. 18,[24][25][26] A study by Pollock et al 20 examined negative reviews in sports medicine and found nonclinical complaints were over three times more common than clinical complaints. Our study found similar results.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…This is especially important in the digital era, where patient satisfaction and dissatisfaction are publicly available on websites such as Healthgrades, Vitals, and Yelp. 21 …”
Section: Introductionmentioning
confidence: 99%
“…In Bernstein's review, most of the studies included that evaluated PRWs of various orthopedic specialties analyzed presence of positive reviews and average physician scores [ 11 ]. In addition, there have been no studies investigating reviews or ratings of orthopedic oncologists [ 11 , 12 ]. The aim of this study is to characterize one-star reviews of orthopedic oncology surgeons to further understand factors that affect the patient experience in this unique patient group.…”
Section: Introductionmentioning
confidence: 99%